IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI SMAS AULIA: Kurikulum Merdeka, implementasi, pembelajaran berdiferensiasi, Profil Pelajar Pancasila, kepemimpinan transformasional - Rahmawati, Ima; Arifin, Zainal; Adawiyah, Fuza Setiawansyah (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
This study aims to describe the implementation of the Independent Curriculum at SMAS Aulia and identify supporting and inhibiting factors in its implementation. The method used is descriptive qualitative with data collection through in-depth interviews, participatory observations, and documentation studies. The research informants consist of principals, teachers, and students who are directly involved in the implementation of the curriculum. The results of the study show that SMAS Aulia has successfully implemented the principles of the Independent Curriculum by emphasizing differentiated and project-based learning. In addition, this school also focuses on strengthening students' character through the Pancasila Student Profile, which is integrated into various learning activities. Transformational leadership of school principals plays a key role in creating a collaborative learning environment and supporting innovation. However, there are several challenges, such as uneven teacher readiness, limited facilities, and teachers' understanding of assessment and teaching planning that is still developing. This research suggests the need to strengthen teacher capacity through continuous training and increased support in terms of educational resources. Overall, the results of this study provide a comprehensive overview of the implementation practice of the Independent Curriculum at SMAS Aulia and the factors that affect its success.